دراسة أثر نوع السماد العضوي في نمو نبات البازلاء صنف روندو - سمرة, بديع; سعيد, هيام (Latakia University Journal -Biological Sciences Series, 2019)
نفذت التجربة خلال الفترة 2009— 2010 في مزرعة فديو التابعة لكلية الزراعة بجامعة تشرين بهدف تحديد أثر نوع السماد العضوي (مخلفات أبقار-سماد أغنام-زرق دواجن) في نمو نبات البازلاء Pissum Sativa صنف روندو حيث تم دراسة جملة من المؤشرات شملت: طول النبات,عدد الأوراق على النبات, طول الورقة, طول السلامية, الوزن الرطب والجاف للنبات, مساحة المسطح الورقي للنبات ودليله وكفاءته التمثيلية . تبين نتيجة الدراسة أن التسميد العضوي قد أدى إلى زيادة في مساحة المسطح الورقي للنبات بمقدار 1581 سم2 و 805 سم2 و88سم2 عند استخدام سماد الأغنام وسماد زرق الدواجن وسماد الأبقار على التوالي مقارنة مع الشاهد غير المسمد بالسماد العضوي. وازدادت كفاءة التمثيل الضوئي الكلية عند استخدام سماد الأغنام بنسبة 116% وعند استخدام زرق الدواجن بنسبة 71% وعند استخدام سماد الأبقار بنسبة 11% مقارنة مع كفاءة التمثيل الضوئي لنباتات الشاهد,. كما ازداد عدد الأوراق على النبات الواحد في سماد الأغنام بنسبة 127 % وفي زرق الدواجن بنسبة 47% مقارنة مع الشاهد, كما كان للتسميد العضوي أثر إيجابي في زيادة الوزن الرطب للنبات حيث بلغت هذه الزيادة 146% عند استخدام سماد الأغنام و 51% عند استخدام زرق الدواجن و21% في حال استخدام سماد الأبقار مقارنة مع وزن نباتات الشاهد. The experiment was carried out during 2009-2010 in Fidio farm belonging to The Faculty of Agriculture, Tishreen University. It tried to identify the effect of type of organic fertilizer (cow dung, sheep discharge, chicken excrement) in growth of green peas pissum sativa. rondo variety. The study was focused on a number of indexes including plant height, number of leaves, leaf length, nod length, fresh and dry weight of plant, total leaf area of the plant and its indication and its photosynthetic efficiency. Results indicated that organic fertilizer yielded a 1581 cm2 increase in total leaf area of the plant after using sheep discharge, a 805 cm2 increase after using chicken excrement and a 88 cm2 after using cow dung, compared with the unfertilized control treatment. The total photosynthetic efficiency increased by 116% after using sheep fertilizer, by 71% after using chicken fertilizer and by 11% after using cow fertilizer when compared with the photosynthetic efficiency of the control sample. Organic fertilizer had a positive effect in increasing the wet weight of the plant at 146% after using sheep fertilizer, 51% after using chicken fertilizer and 21% after using chicken fertilizer compared with the control sample.